Pengaruh Substitusi Agregat Kasar PET terhadap Kuat Tekan Beton Normal 7 Hari: Evaluasi Pengaruh Variasi Persentase PET terhadap Kuat Tekan Beton Normal 7 Hari - Pramudya Kurniawan; Ikhwan Arief Purnama; Dimas Nugroho; Sri Wahyuni Ravika (Teknik Sipil, Politeknik Negeri Ketapangg, 2026)
Polyethylene Terephthalate (PET) is a type of plastic waste that degrades very slowly and has the potential to cause environmental pollution. The use of PET as an artificial aggregate in concrete mixtures is an alternative to reduce dependence on natural aggregates while minimizing negative impacts on the environment. This study aims to evaluate the effect of coarse aggregate substitution using PET on the compressive strength of concrete at 7 days of age. Cylindrical test specimens measuring 15 × 30 cm were made with PET substitution variations of 0%, 5%, 10%, 15%, 20%, and 25%. Compressive strength testing was carried out at 7 days with a target compressive strength of 20 MPa. The test results showed a decrease in compressive strength as the PET substitution content increased. Normal concrete had an average compressive strength of 24.89 MPa, while 5% substitution resulted in 20.38 MPa and 10% substitution resulted in 17.39 MPa, which still met the planned compressive strength range. At 15% substitution, the compressive strength decreased to 16.10 MPa, at 20% to 14.80 MPa, and at 25% to 11.80 MPa. Based on these results, the use of PET as a partial replacement for coarse aggregate is considered effective up to a substitution limit of 5%–10%.